2012
DOI: 10.1152/japplphysiol.00151.2012
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training and muscle microvascular oxygenation: functional role of nitric oxide

Abstract: Exercise training induces multiple adaptations within skeletal muscle that may improve local O(2) delivery-utilization matching (i.e., Po(2)mv). We tested the hypothesis that increased nitric oxide (NO) function is intrinsic to improved muscle Po(2)mv kinetics from rest to contractions after exercise training. Healthy young Sprague-Dawley rats were assigned to sedentary (n = 18) or progressive treadmill exercise training (n = 10; 5 days/wk, 6-8 wk, final workload of 60 min/day at 35 m/min, -14% grade) groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
70
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(77 citation statements)
references
References 68 publications
5
70
2
Order By: Relevance
“…Although the effects of EX on capillary hemodynamics (59,69), microvascular remodeling, and capillarity (45,125) have been characterized under normal circumstances, fewer studies have been conducted in patients with T2D. Observations of slowed oxygen kinetics at the onset of exercise and decreased skeletal muscle blood flow during exercise in patients with T2D (13,70,76,129,152) may be explained, in part, by decreased capillary perfusion.…”
Section: Ex Smooth Muscle and Capillary Function And Vascular Remodmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the effects of EX on capillary hemodynamics (59,69), microvascular remodeling, and capillarity (45,125) have been characterized under normal circumstances, fewer studies have been conducted in patients with T2D. Observations of slowed oxygen kinetics at the onset of exercise and decreased skeletal muscle blood flow during exercise in patients with T2D (13,70,76,129,152) may be explained, in part, by decreased capillary perfusion.…”
Section: Ex Smooth Muscle and Capillary Function And Vascular Remodmentioning
confidence: 99%
“…Although total hind limb blood flow at rest and during submaximal exercise was not different between control and T2D rats (regional differences were present) (33), differences in capillary perfusion at rest may contribute to impaired matching of oxygen delivery with utilization resulting in exercise intolerance and decreased glucose delivery/uptake in skeletal muscle. Hirai and colleagues (59) reported that, in healthy rats, progressive moderate to vigorous downhill running endurance EX improved microvascular oxygenation profiles following the onset of skeletal muscle contraction, partially through an NO mechanism. Furthermore, similar improvements were observed in rats with chronic heart failure but did not appear to be NO mediated (60).…”
Section: Ex Smooth Muscle and Capillary Function And Vascular Remodmentioning
confidence: 99%
See 1 more Smart Citation
“…Key questions posed in the 2012 review (248) have been addressed; especially regarding the plasticity of Q mO 2 in response to exercise training and novel therapeutic strategies. For instance, in contrast to healthy animals it is now apparent that exercise training in CHF (reduced ejection fraction) acts to raise P mvO 2 , in part, via non-NO-mediated effects (134,136). Additionally, inorganic nitrate supplementation (NO source) has proven to be especially effective in raising blood flow (Q m ) and Q mO 2 to fast-twitch muscle fibers in healthy animals (76, 77) and improving cardiac output, V O 2max , and exercise capacity in CHF patients (CHF with preserved ejection fraction; Ref.…”
mentioning
confidence: 99%
“…Although exercise rehabilitation represents an effective therapeutic modality for treating CHF (9), reduced NO bioavailability in CHF is associated with an impaired ability to perform exercise and/or even complete daily physical activities. Consequently, interventions that increase NO bioavailability may ameliorate the skeletal muscle vascular dysfunction evident in this disease (20,25) and thus have great potential to improve exercise tolerance and quality of life in this population.NO is synthesized endogenously via three isoforms of NO synthase (NOS) as well as by the nonenzymatic reduction of NO 3 Ϫ to NO 2 Ϫ and, finally, to NO (for a review, see Ref. 38).…”
mentioning
confidence: 99%